Are mutual fund fees excessive? - Adams, John C.; Mansi, Sattar A.; Nishikawa, Takeshi (Journal of Banking & Finance, 2012)
There is a long running debate over whether competition in the mutual fund industry limits the ability of investment advisors to charge fees that are disproportionate to the services they provide. We posit that disproportionately high fees are prevalent in funds with multiple share classes and those with weak governance structures. Using a comprehensive sample of index mutual funds for the from 1998 to 2007, we find that internal governance mechanisms matter primarily for funds with relatively small share classes where investors often face increased search costs and/or restricted access to competitive mutual funds. Additionally, we find that funds managed by publicly held sponsors are associated with disproportionately higher fee spreads (about 28 basis points). The results are robust to the inclusion of board characteristics, share class structure, and investment objectives. Overall, our findings suggest that competition and agency considerations are important determinants in the pricing of mutual funds.